THE USE OF OZONE THERAPY IN MUSCULOSKELETAL DISEASES: PHYSICAL THERAPY INTERVENTION - Amato, Camila Zanete; Emerick, Daniela Brum; Corrêa, Douglas Xavier; Gervasio, Gleiciane das Graças; Oliveira, Jorciane Félix Pinheiro; Lopes, Kamila Emilly Ferreira Gonçalves; Souza, Lucas Neves de Oliveira; Júnior, Orlando Alves de Almeida; Pereira, Roberto Carlos Lopes; de Oliveira, Sara Carvalho; de Abreu, Enrico Lopes Campos; de Abreu, Juscélio Clemente (Seven Editora, 2024)
Ozone therapy has been established as an innovative therapeutic approach, especially in the treatment of musculoskeletal diseases. This technique consists of applying a mixture of oxygen (O₂) and ozone (O₃), generated by specific equipment, which has analgic, anti-inflammatory and antioxidant effects, and is minimally invasive. This chapter discusses the mechanisms of action and application of ozone therapy, its indications and contraindications, and compares it with other treatment modalities used in the physical therapy approach to musculoskeletal diseases. DOI:https://doi.org/10.56238/sevened2024.037-069